2023
DOI: 10.1371/journal.pgen.1010595
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic ribosomal protein S6 (Rps6) insufficiency results in failed bile duct development and loss of hepatocyte viability; a ribosomopathy-like phenotype that is partially p53-dependent

Abstract: Defective ribosome biogenesis (RiBi) underlies a group of clinically diverse human diseases collectively known as the ribosomopathies, core manifestations of which include cytopenias and developmental abnormalities that are believed to stem primarily from an inability to synthesize adequate numbers of ribosomes and concomitant activation of p53. The importance of a correctly functioning RiBi machinery for maintaining tissue homeostasis is illustrated by the observation that, despite having a paucity of certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 166 publications
1
2
0
Order By: Relevance
“…This type of clonal regenerative nodes rescuing liver function also occurs in several other knockout genetic models [52,59]. It was shown that this surviving tissue represents the clonal expansion of mutated hepatocytes that managed to evade recombination and restore the initial levels of the targeted protein, however, other compensatory mechanism could also be involved [52,59]. We demonstrate that PARG-targeted recombination happened in these nodes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This type of clonal regenerative nodes rescuing liver function also occurs in several other knockout genetic models [52,59]. It was shown that this surviving tissue represents the clonal expansion of mutated hepatocytes that managed to evade recombination and restore the initial levels of the targeted protein, however, other compensatory mechanism could also be involved [52,59]. We demonstrate that PARG-targeted recombination happened in these nodes.…”
Section: Discussionsupporting
confidence: 57%
“…These hepatocytes do not display the hypertrophic phenotype, instead, they divide and eventually replace the entire liver tissue. This type of clonal regenerative nodes rescuing liver function also occurs in several other knockout genetic models [52,59]. It was shown that this surviving tissue represents the clonal expansion of mutated hepatocytes that managed to evade recombination and restore the initial levels of the targeted protein, however, other compensatory mechanism could also be involved [52,59].…”
Section: Discussionmentioning
confidence: 82%
“…Mdm2 gene amplification is the main mechanism of oncogenic activation [104]. MYC induction enhances the RiBi and stability of the p53 protein, while MYC silencing reduces the expression of RPL5, RPL11, and 5S rRNA in IRBC complexes [105], resulting in a rapid decrease in the p53 protein half-life in a human double minute 2 (HDM2)-dependent manner [106]. RPL5 and RPL11 inhibit MYC transcription and destroy the stability of MYC mRNA, forming a negative feedback loop [104,107].…”
Section: Myc-induced Impaired Irbc May Be a Potential Target For Canc...mentioning
confidence: 99%
“…The major pathway that RPS6 involved in is the PI3K/Akt/mTOR pathway, in which RPS6 interacts with and activates mTOR to promote protein synthesis and cell growth 20 . Alternatively, RPS6 could also inhibit the tumor suppressive function of TP53 to increased risk of tumorigenesis 44 (Figure 3E). Taken together, the superiority of ChatGPT in literature searching and logic presentation liberates human scientists from time-consuming and tedious document work.…”
Section: Classification Of Scc Patients Into Clinically Interpretable...mentioning
confidence: 99%